The Bacterial Contamination of the Operating lounges in Hospitals of Al-Diwaniyah Province with the Two types of Intestinal E.coli and St.aureus Cutaneous. - salwan abdul muaen; Fallah H.Abdullatef; Bassim M. Al-khafaji; Anwar H. Jawad; Qassim J. Talib (Al-Qadisiyah Journal of Pure Science, 2020)
The research aims to study the bacterial contamination of the two types, E.coli and St.aureus, which are endemic in the lobbies and halls of operations and childbirth in the hospitals of Al-Diwaniyah province, where 4475 samples were isolated from governmental and private hospitals throughout the province from October 2019 to September 2020, where The study included taking samples from six hospitals in the city center and three in the districts and sub-districts of the governorate. (20.26%), Women's and Children's Hospital (19.74%), Al-Diwaniyah Teaching Hospital (19.33%), Hamza Hospital (17.64%), the Middle Euphrates Al-Ahli 13.02, and finally Al-Diwaniyah National Hospital (4.92%), which had the lowest level of injury. The rates of infection in the two types of bacteria under study varied, as little difference was observed between the level of contamination of the two types within the same site, and the burn center also showed a high rate of contamination compared to the rest of the sites.